RISK FACTORS IN ECTOPIC PREGNANCY - F oskouie; H Ahmadnia; Z Feizi; H Haghani (Iran University of Medical Sciences, 2001)
Background : Ectopic pregnancy is one of the medical and serious threatening problem to women's life at the present time, It's risk factors have discussed since ancient times.   Objective : To determine the risk factors of ectopic pregnancy.   Design : This research was a case- control study. The information about the case group (ectopic pregnancy) and the control group (normal delivery) were gathered form the medical charts, between 1995 to 2000, and were recorded in the data record sheet that was composed of 4 parts: demographic, individual characteristics, infertility treatment technologies and contraceptive methods. The variables were statistically analyzed in two group.   Samples : The all of 290 women with ectopic pregnancy who had been hospitalized in the central and southern districts of Tehran mead the case group and 870 women who had normal delivery at the same time were selected randomly as the control group of this study.   Results : The finding showed that there were statistically signification between ectopic pregnancy and following variables: age, parity, the history of pelvic, abdominal and tubal surgeries and pelvic inflammatory disease, history of infertility, smoking and the use of contraceptive methods with the happening of pregnancy concurrently.   Conclusion : According to the results of this study, older ages, ground parity, history of ectopic pregnancy, pelvic, abdominal and tubal surgery, pelvic inflammatory disease, history of infertility, smoking and failure of contraceptive methods were confirmed as risk factors for ectopic pregnancy. It is recommended that the risk factors of ectopic pregnancy be assessed in all of pregnant women who come to prenatal care unit in early pregnancy by use of a short questionnaire, It is also recommended to study the risk of each factors by two matched group prospectively.